2016
DOI: 10.1002/mame.201600125
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐Permeable Cellulose Template for Reduction of Template Damage and Gas Trapping in Microimprint Lithography of High Volume Manufacturing

Abstract: A gas‐permeable cellulose template for microimprint lithography has been synthesized and characterized for the reduction of template damage and gas trapping caused by solvents and oxygen generated from cross‐linked materials. The 5 μm line‐pattern failure of the microimprinted UV cross‐linked liquid materials with 4.7 wt% acetone as a volatile solvent is solved by using the gas‐permeable cellulose template because of its increased oxygen permeability. The gas‐permeable cellulose template also allows the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…The gas-permeable template data and Young's modulus data used to support the findings of this study were cited at relevant places within the text as references [1][2][3][4][5][6][7]20].…”
Section: Data Availabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The gas-permeable template data and Young's modulus data used to support the findings of this study were cited at relevant places within the text as references [1][2][3][4][5][6][7]20].…”
Section: Data Availabilitymentioning
confidence: 99%
“…A gas-permeable template shown in Figure 1 has attracted attention as a method to reduce pattern defects caused by air trapping and outgas generated by solvents between a template and an imprinting material [1][2][3][4][5][6][7]. The gas-permeable template increases the area required for mass production owing to lower mechanical properties as compared with those of a non-gas-permeable metallic template.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we reported a gas permeable mold derived from cellulose reduces the void caused by the outgas from acrylic material including 4.9 wt% of acetone [15]. Figure 1 shows the comparison between the gas impermeable mold and the gas permeable mold in IL process.…”
Section: Introductionmentioning
confidence: 99%
“…Gas permeable templates avoid transfer defects and template damage from gases, e.g., nitrogen and oxygen, which are generated from the resist materials [7][8][9]. Takei et al developed a gas permeable template obtained from plant-derived materials to address the transfer failure caused by the trapped air and gas between the mold and substrate [10][11][12][13][14][15]. The authors also measured the mechanical strength, light trans -mittance, and gas permeability of the template materials using a plant-derived material and their transferability to the target material containing a volatile solvent [16].…”
Section: Introductionmentioning
confidence: 99%